Social Networks and Educational Decisions: Who has Access to Social Capital and for Whom is it Beneficial? - Sven Lenkewitz; Mark Wittek (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
This article investigates students' access to social capital and its role in their educational decisions in the stratified German school system. We measure social capital as the availability of highly educated adults in adolescents' and parents' social networks. Using panel data on complete friendship as well as parental networks and the educational decisions of more than 2700 students from the CILS4EU-DE dataset, we show that social networks are segregated along socio-economic differences, which restricts access to social capital for socio-economically disadvantaged students. A~comparison shows that parental networks tend to be substantially more segregated than children's friendship networks. In addition, our results indicate that access to social capital is linked to academically ambitious choices—i.e., entering upper secondary school or enrolling in university. This relationship is especially pronounced for less privileged students.
Keywords: 300; Educational inequality; Educational stratification; Parental networks; Academically ambitious decisions; Exponential random graph model; Bildungsungleichheit; Bildungsstratifikation; Elternetzwerke; Ambitionierte Bildungsentscheidungen; ERGM